Gambaran Tingkat Stres pada Mahasiswa Fakultas Kedokteran Universitas Riau Tahun Pertama - Rony Wahyudi; Eka Bebasari; Elda Nazriati (Fakultas Kedokteran Universitas Riau, 2015)
The prevalence of stress on medical students is very high, especially on first grade medical students. Theproblem to adapt to new environment is the most common cause of stress occuring on first grade medicalstudents. Stress can become negative effect to person. The aim of this study was to understand the stresslevels on first grade medical students of Faculty of Medicine, University of Riau. This study used descriptivedesign with cross-sectional approach. Samples in this study were 166, using total sampling technique. Datawas accumulated by using Medical Student Stressor Questionnaire (MSSQ) that had been modified forstress levels. The results showed that 57.23% had moderate stress levels with stressors related academicand stressors related teaching-learning relationship as the highest stressors.